2017
DOI: 10.1016/j.canlet.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressor SPOP ubiquitinates and degrades EglN2 to compromise growth of prostate cancer cells

Abstract: EglN prolyl hydroxylases, a family of oxygen-sensing enzymes, hydroxylate distinct proteins to modulate diverse physiopathological signals. Aberrant regulations of EglNs result in multiple human diseases, including cancer. Different from EglN1 which function largely depends on the role of hypoxia-induce factor alpha (HIFα) in tumors, the functional significance and the upstream regulatory mechanisms of EglN2, especially in prostate cancer setting, remain largely unclear. Here, we demonstrated that dysregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…[25][26][27] Recently, it was demonstrated that SPOP plays a tumor suppressive role in prostate and endometrial cancers and a tumor-promoting role in kidney cancer. [28][29][30][31] In this study, we report that SPOP participates in TLR-mediated signaling. We identified SPOP as a MyD88-associated protein with yeast two-hybrid technology.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Recently, it was demonstrated that SPOP plays a tumor suppressive role in prostate and endometrial cancers and a tumor-promoting role in kidney cancer. [28][29][30][31] In this study, we report that SPOP participates in TLR-mediated signaling. We identified SPOP as a MyD88-associated protein with yeast two-hybrid technology.…”
Section: Introductionmentioning
confidence: 99%
“…Also, PHD1 has been recently demonstrated to be targeted for degradation by an E3 ubiquitin ligase called speckle‐type POZ protein (SPOP), which is commonly mutated in prostate cancer (Zhang et al . ). In SPOP‐deficient prostate cancer cells, knockdown of PHD1 was sufficient to dampen increased cell colony formation introduced by loss of SPOP, thus implying an oncogenic role of PHD1 in that setting (Zhang et al .…”
Section: Molecular Oxygen Sensing In Metazoan Cellsmentioning
confidence: 97%
“…In SPOP‐deficient prostate cancer cells, knockdown of PHD1 was sufficient to dampen increased cell colony formation introduced by loss of SPOP, thus implying an oncogenic role of PHD1 in that setting (Zhang et al . ). In addition, FBW7, another E3 ubiquitin ligase, negatively regulates PHD1 protein expression in an in vitro model of triple receptor‐negative breast cancer (Takada et al .…”
Section: Molecular Oxygen Sensing In Metazoan Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…SPOP suppresses tumorigenesis and progression via regulation of cell growth, apoptosis, migration, invasion and drug resistance by targeting its downstream substrates in several types of human malignancies, including prostate, lung, gastric, liver, colon and endometrial cancers SPOP mutations and downregulation were detected in human PrCa tissues, and these mutations were also tightly correlated with a worse prognosis in patients with PrCa [61]. More importantly, extensive biochemical evidence has further indicated that SPOP functions as a tumor suppressor by promoting the degradation of oncogenic substrates in PrCa, including SRC3 [62], AR [63], TRIM24 [64], c-Myc [65], DEK [66], SENP7 [67], EglN2 [68], ATF2 [69], Cdc20 [70], ERG [71,81], BRD4 [72][73][74], PD-L1 [75] and cyclin E1 [76]. Due to the many publications and space limitations, we will not describe the tumor suppressive role that SPOP plays by promoting the ubiquitination and degradation of its substrates in PrCa in detail.…”
Section: Prostate Cancer (Prca)mentioning
confidence: 99%